In utero pyrethroid pesticide exposure in relation to autism spectrum disorder (ASD) and other neurodevelopmental outcomes at 3 years in the MARBLES longitudinal cohort - Barkoski, Jacqueline M.; Philippat, Claire; Tancredi, Daniel; Schmidt, Rebecca J.; Ozonoff, Sally; Barr, Dana Boyd; Elms, William; Bennett, Deborah H.; Hertz-Picciotto, Irva (Environmental research, 2021)
We assessed the relationships between prenatal pyrethroid pesticide exposure and autism spectrum disorders (ASD) or non-typical development (non-TD) at 3 years. Participants were mother-child pairs (n = 201) in the MARBLES (Markers of Autism Risk in Babies-Learning Early Signs) cohort. Because familial recurrence risk is high, MARBLES enrolls pregnant women with a family history of ASD. Children from these pregnancies were clinically assessed at 3 years of age and classified into 3 outcome categories: ASD, typically developing (TD), or non-TD (neither TD or ASD). Repeated maternal second and third trimester urine samples were analyzed for pyrethroid metabolite 3-phenoxybenzoic acid (3-PBA). Multinomial logistic regression was used to obtain relative risk ratios (RRR) linking 3-PBA concentrations averaged across each trimester and over pregnancy with child's outcome: ASD or non-TD vs. TD. Models were adjusted for specific gravity, maternal pre-pregnancy BMI, prenatal vitamin use, birth year, home-ownership, and pregnancy concentrations of TCPy (3,5,6-trichloro-2-pyridinol, a metabolite of chlorpyrifos). The median specific gravity corrected 3-PBA concentration of all samples was 1.46 ng/mL. Greater second trimester 3-PBA concentrations were associated with a relative risk ratio (RRR) for ASD of (RRR: 1.50 (95% CI 0.89 to 2.51), p = 0.12). There were no differences between non-TD and TD. This study found no evidence for differences in 3-PBA comparing non-TD with TD. A modestly elevated RRR was found comparing second trimester urinary 3-PBA concentrations for ASD versus TD; however, the confidence interval was wide and hence, these findings cannot be considered definitive. •First study of pregnancy pyrethroid pesticide biomarker and risk of ASD at 3-years.•Higher concentration of urinary 3-PBA associated with modest increased risk for ASD.•Pesticide exposure characterization difficult due to temporal variability and multiple sources.